2015
DOI: 10.1021/acs.energyfuels.5b01127
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-Enhanced Liquefaction of Lignin with Formic Acid as an in Situ Hydrogen Donor

Abstract: The conversion of bio-mass into bio-fuel using solvents that come from bio-mass itself is being more and more important for the concern of renewable development and CO 2 -netural. Formic acid was used as an in situ hydrogen donor for the liquefaction of wheat straw alkali lignin. It was found that the addition of ethanol improved the yield of mono-phenols remarkably. Although ethanol exhibited a poor effect in the liquefaction of lignin, it was found to be a good assistant solvent for improving the mono-phenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 21 publications
1
20
0
Order By: Relevance
“…The valorization of lignin has several applications, such as synthesis of bio‐oil, phenolic resins, adhesives of polyurethane foams, carbon fiber, etc. One of the significant conversion pathways for lignin is liquefaction which generates bio‐oil and phenolic monomers . The development of lignin liquefaction process can considerably help to increase the commercial value of lignin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The valorization of lignin has several applications, such as synthesis of bio‐oil, phenolic resins, adhesives of polyurethane foams, carbon fiber, etc. One of the significant conversion pathways for lignin is liquefaction which generates bio‐oil and phenolic monomers . The development of lignin liquefaction process can considerably help to increase the commercial value of lignin.…”
Section: Introductionmentioning
confidence: 99%
“…One of the significant conversion pathways for lignin is liquefaction which generates bio-oil and phenolic monomers. [9][10][11][12] The development of lignin liquefaction process can considerably help to increase the commercial value of lignin. However, new strategies are required to substitute lignin as raw material alternative to fossil feedstocks because of the high oxygen content, complex structure of lignin, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen donor molecules are thought to convert lignin through catalytic transfer hydrogenation mechanisms or act as an in situ hydrogen source for lignin hydroprocessing [93][94] . In some cases a solvent is used to improve the heat and mass transfer rates and enhance the miscibility of the reaction mixture 93,[95][96] . Low molecular weight alcohols, such as ethanol, methanol and isopropanol, ionic liquids and water are among the preferred choices 8 .…”
Section: Reductive Methodsmentioning
confidence: 99%
“…This hydrogen donor molecule decomposes mainly into molecular hydrogen and CO 2 under the LtL conditions creating a reductive environment (low amounts of CO and H 2 O are also produced). Most of the researchers believe that formic acid act either as an in-situ hydrogen source or a hydrogen donor molecule through catalytic-hydrogen transfer reactions 93,96,[138][139][140] . However, its role in the lignin conversion process is not fully understood and there are no published mechanisms that can explain why formic acid is more active than other hydrogen donors.…”
Section: Lignin-to-liquid Concept (Ltl)mentioning
confidence: 99%
“…The synergistic effect of water/ethanol mixture in the liquefaction of rice husk for bio-oil production via the HTL process was also observed by Liu et al (2013). Besides the high bio-oil yield, the addition of ethanol to water also affects the distribution of phenolics such as phenol, ethylphenol and guaiacols, ethylguaiacol and syringol in the bio-oil as well (Ye et al 2012, Ouyang et al 2015). Recently, Kosinkova et al (2015) reported that aqueous ethanol improved the higher heating value (HHV) of bio-oil to be used in the field of biodiesel applications.…”
Section: Introductionmentioning
confidence: 84%